THE STRUCTURE AND CHEMICAL COMPOUND OF THE LONG BONES UNDER CONDITIONS OF USAGE HEAVY METAL SALTS - Васько, Л.В.; Kiptenko, L.I.; Gortinskaya, O.M. (World of Medicine and Biology, 2012)
In article the influence of salts of zinc, chrom and plumbum on growth and structure of long bones of a skeleton is investigated. Was studied bones’ osteometria, gistological structure of the diaphisis and epiphiseal cartilage with subsequent them mophometria which spent on a standard technique. The revealed changes testify to a delay of longitudinal growth of bones and change of their structure as distrophic and destructial changes. In the readaptation period there is no complete restoration growth and gistological parameters of the osseous tissues.